Neurofilament light chain levels in neuronal surface antibody-associated autoimmune encephalitis: a systematic review and meta-analysis - Qi-Lun Lai; Meng-Ting Cai; Er-Chuang Li; Gao-Li Fang; Chun-Hong Shen; Yong-Feng Xu; Song Qiao; Jia-Jia Wang; Qin-Jie Weng; Yin-Xi Zhang (Translational Psychiatry)
Abstract Background Neuronal surface antibody-associated autoimmune encephalitis (NSAE) is a group of neuro-inflammatory disorders that is mediated by autoantibodies against the cell-surface and synaptic antigens. Studies have explored the role of neurofilament light chain (NfL) in NSAE and provided inconsistent data. We performed a systematic review and meta-analysis to evaluate the NfL levels in the serum and cerebrospinal fluid (CSF) of patients with NSAE. Methods The National Center for Biotechnology Information (NCBI, PubMed), Web of Knowledge, and the Cochrane Library databases were searched for studies reporting NfL levels in patients with NSAE. Random-effects meta-analysis was used to pool results across studies. Results Thirteen studies were included in the final systematic review and meta-analysis. The serum NfL levels were significantly higher in patients with NSAE compared to unaffected controls (standardized mean difference [SMD] = 0.909, 95% confidence interval [CI]: 0.536–1.282). Similarly, the CSF NfL levels were elevated in patients with NSAE (SMD = 0.897, 95% CI: 0.508–1.286). The serum and CSF NfL levels were not significantly correlated with disease severity, prognosis, and abnormalities in magnetic resonance imaging, electroencephalography, and CSF. Conclusions NfL levels in the serum and CSF were higher in patients with NSAE compared to unaffected controls. However, the NfL levels were not shown to be significantly associated with clinical or paraclinical features.